Cerebellar infarction complicated with acute hydrocephalus - Rosyidi, Rohadi M.; Priyanto, Bambang (International Journal of Research in Medical Sciences, 2019)
Acute hydrocephalus is a rare manifestation of posterior circulation strokes. Clinical worsening and coma may occur in addition to these symptoms of cerebellar dysfunction. Timely and careful approach will certainly prove to be life saving when deciding for a shunt procedure in a patient developing obstructive hydrocephalus following cerebellar infarct. The case presented here is a reminder for both this rare complication, and the treatment approach. We present a patient with cerebellar infarct and secondary obstructive hydrocephalus. Forty three year old male patient was brought to the emergency room in our hospital with unconsciousness, before that patient with suddenly developing dizziness, loss of balance and vomiting. His neurological examination showed that he was coma. The patient's brain computed tomography scan showed severe third and lateral ventricular dilation suggestive of obstructive hydrocephalus. Following shunt placement and suboccipital decompression, the patient recovered and was able to walk without assistance. Cerebellar infarcts may cause death as a result of pressure increase in the posterior fossa and pressure on the brain stem due to edema. Moreover, the aquaductus or the fourth ventricle may close because of edema and cause obstructive hydrocephalus and acute intracranial pressure increase. Temporary external ventricular drainage or permanent shunt systems and surgical decompression of the posterior fossa may be considered to prevent progressive neurologic worsening. In conclusion, we wished to point out that a timely surgical procedure in a cerebellar infarct case where acute hydrocephalus developed could be life saving.